Severe Varicella-Zoster virus pneumonia in a healthy young adult treated with acyclovir and extracorporeal membrane oxygenation: a case report: Prikaz primera hudega poteka pljučnice povzročene z virusom Varicella-Zoster, zdravljene z aciklovirjem in zunajtelesno membransko oksigenacijo - Varda, Luka; Omerović, Metin; Kit, Barbara; Svenšek, Franc; Fluher, Jure; Cestar, Iva; Marinšek, Martin; Markota, Andrej (Acta Medico-Biotechnica, 2024)
Purpose: Varicella-zoster virus (VZV) infection is common in children and is usually benign. In adults VZV infection can present as a severe primary viral pneumonia with acute respiratory failure. VZV infections in adult have a high mortality rate.Case report: A 32-year-old previously healthy male first presented to the emergency department with flulikesymptoms and no rash. Three days later he returned to the emergency department with a disseminatedskin rash and severe acute respiratory distress syndrome that required intubation and mechanical ventilation. A VZV infection was confirmed. Mechanical ventilation was insufficient and venovenous extracorporeal membrane oxygenation was introduced. In addition to supportive measures, he was treated with intravenousacyclovir. During hospitalisation he developed several complications, including severe cor pulmonale necessitating treatment with nitrous oxide and milrinone, disseminated intravascular coagulation necessitating an extracorporeal membrane change, and ventilator-associated pneumonia. He was discharged home in stable condition on hospital day 27.Conclusion: Primary VZV infection in adulthood is associated with several complications. Early recognition ofacute respiratory failure, ventilatory support, and early administration of acyclovir are crucial elements of VZVpneumonia treatment.
Keywords: Varicella-zoster virus; pneumonia; extracorporeal membrane oxygenation; cor pulmonale; case report